Phenomenological application of the projection-operator method and its connection with critical dynamics - Sardella, Edson [UNESP] (American Physical Society (APS), 1991)
We consider the dynamics of a system of interacting spins described by the Ginzburg-Landau Hamiltonian. The method used is Zwanzigs version of the projection-operator method, in contrast to previous derivations in which we used Moris version of this method. It is proved that both methods produce the same answer for the Greens function. We also make contact between the projection-operator method and critical dynamics. © 1991 The American Physical Society.